Assistance Of Primary School Age Children (6-12 Years) Education And Capacity Building In The Village Dringu - Faridahtul Jannah; Shofia Hattarina; Isslandy Ayu Hermalia; Pangestu Nur Rizky; Vega Fakis Alhamni (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
The aims of program to technical assistance to of primary school age children. By the presence of assistance is expected to increase the motivation of students to study. This devotion activities will be integrated with children for the empowerment activities conducted by lecturers and students from Universitas Panca Marga. The goal is to combine the resources and information to unite of motion in the program activities cooperation and complement each other in empower Dringu children. This activities devotion will be more efficient in terms of time and more to. The original target of activities are children devotion elementary school that is in assistance to the teams. It would build a devotion awareness of children and their parents will be the importance of the education of their children. The children will be eager to study and developing themselves. The results of devotion to explain the dynamics of flanking process includes: variety of the activities that were undertaken, forms the action of technical or stunt the program to break up